An exploratory study on socio-economic status of Malay women entrepreneurs in Penang: a case of ICT-based business / Nurwahida Fuad, Abdul Manaf Bohari and Cheng Wei Hin - Fuad, Nurwahida; Bohari, Abdul Manaf; Cheng, Wei Hin (Universiti Teknologi MARA, Perlis, 2011)
Recently, women entrepreneur has contributes important part to the nation growth of Malaysia which has participates in the ICT-related business such as Telecommunication Devices, Hand Phone Shop, Computer Accessories, Cyber Cafe, ICT-based Training, Photography Shop, Kiosk, and many more. Although women entrepreneur in Malaysia is highlighted as have significance contribution toward the nation economic performances, however, research is still lacking regarding the socio-economic status of Malay women entrepreneurs especially in Penang. The major question is what is the current socio-economic status of Malay women entrepreneurs in Penang, as implications of most of the business sector in Penang is dominating by nonMalay businesses as well as Chinese, Indian Muslim, and so on. Common issues analyzed in the previous literature include gender and personal characteristics such as level of education, experience, family size, age, marital status, and so on. The objective of this research is to develop a demographic profile revealing socioeconomic status of the Malay women entrepreneur. This study was conducted among 150 malay women entrepreneurs in Penang State of Malaysia that were listed in the major websites such as website of Society of Penang ICT Entrepreneurs (Persatuan Usahawan ICT Pulau Pinang), Portal Usahawan Bumiputera Pulau Pinang and Online Directory of Entrepreneurs of Penang. The exploratory study was choosing as research design. Specifically, the sample was carried out among the business who has conducted the ICT-related business where information regarding socio-economy status of them is very limited. The analysis highlights the complexity of demographic issues among Malays women entrepreneur of Penang. The implications of this study are briefly explored.